2004
DOI: 10.1590/s0004-282x2004000100023
|View full text |Cite
|
Sign up to set email alerts
|

Estudo ultra-estrutural do processo remielinizante pós-injeção de brometo de etídio no tronco encefálico de ratos imunossuprimidos com dexametasona

Abstract: RESUMO -Linfócitos estão presentes nas lesões desmielinizantes induzidas pelo brometo de etídio (BE) no sistema nervoso central (SNC) e a possibilidade de sua participação em eventuais respostas imunomediadas às bainhas de mielina desprendidas não pode ser descartada. Este estudo objetivou investigar as conseqüências da imunossupressão com dexametasona no reparo do SNC após injeção local de BE. Ratos Wistar adultos receberam 10 microlitros de solução de BE a 0,1% na cisterna pontis. Alguns destes foram tratado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
(37 reference statements)
2
11
2
1
Order By: Relevance
“…The finding of huge amounts of myelin-derived membranes in the PNS demyelinating lesions of diabetic rats resembled the one observed in the brainstem of rats immunosuppressed with cyclophosphamide 3 or dexamethasone 4 as well as in streptozotocin-diabetic rats 5 in which was observed a delay in the scavenging activi-ty of macrophages and in the subsequent CNS remyelinating process. Short-term diabetes mimics lesions of slow development induced by EB in the rat CNS and delays all the subsequent repair events 5 .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The finding of huge amounts of myelin-derived membranes in the PNS demyelinating lesions of diabetic rats resembled the one observed in the brainstem of rats immunosuppressed with cyclophosphamide 3 or dexamethasone 4 as well as in streptozotocin-diabetic rats 5 in which was observed a delay in the scavenging activi-ty of macrophages and in the subsequent CNS remyelinating process. Short-term diabetes mimics lesions of slow development induced by EB in the rat CNS and delays all the subsequent repair events 5 .…”
Section: Discussionsupporting
confidence: 71%
“…Several studies reported the invasive capacity of Schwann cells into the CNS from spinal or cranial nerves due to the glia limitans disruption following injection of the gliotoxin [1][2][3][4][5] . This invasion however appeared to be diminished in the diabetic state induced by streptozotocin treatment 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized as an auto-immune disease that causes destruction of oligodendrocytes and, consequently, loss of the myelin sheath. This myelin loss causes a great variability of pathologic conditions [2][3][4] . Although its etiology is unknown 5 , it is postulated that genetic and environmental factors causes self-destructive lesions in the central nervous system, specifically against the white matter [5][6][7] .…”
Section: Ft Cíntia Cristina Souza Nassar -Rua Voluntários Da Pátria mentioning
confidence: 99%
“…Numerous experimental models that simulate the pathophysiology of the demyelinating process of Ms have been developed. ethidium bromide (eB) is a gliotoxic drug that induces demyelination 2,3 and it is a well described model that has improved the comprehension of the biologic process of central nervous system (cNs) demyelination [11][12][13] .…”
Section: Ft Cíntia Cristina Souza Nassar -Rua Voluntários Da Pátria mentioning
confidence: 99%